Kontradyktoryjność postępowania apelacyjnego – wybrane zagadnienia - Rzewuski, Maciej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Among the particular branches of law, one can distinguish the so-called primary principles of law. They mirror the basic assumptions of a specific area of law. Adversarial principle is regarded as one of such principles within the field of civil proceeding. In the most general approach, the principle indicates the burden that rests on the parties – presenting factual situation and invoking evidence to support it. Under this rule, the cognition of civil court is limited solely to assessing the evidence introduced by parties and providing a suitable decision on this basis. Introduction of the adversarial principle ought to significantly contribute to creating a quick and efficient mechanism for bringing to justice based on evidence invoked by the parties. Winning the court case ought to constitute a reward for appropriate fulfillment of one’s law-imposed obligation to present rationale.